Non-isothermal sheath model for low pressure plasmas. (25th July 2019) - Tavant, Antoine; Lucken, Romain; Bourdon, Anne; Chabert, Pascal
Abstract: The evolution of the electron mean energy in the pre-sheath and the sheath of a low pressure plasma bounded by two planes is investigated with 1D particle in cell simulations. We observed that the electron mean energy is not constant in the sheath, but instead decreases significantly from the bulk towards the wall. From the simulations, a polytropic state law is proposed, allowing us to close the fluid equations for the electrons without the isothermal hypothesis. A comparison between the fluid model and the simulations show that the non-isothermal sheath model is more accurate than the isothermal model. The impact of the electron mean energy variation on the potential sheath drop and the electron particle and heat flux is evaluated.